2013
DOI: 10.4269/ajtmh.12-0425
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Indicator Bacteria Contamination of Fomites and Household Demand for Surface Disinfection Products: A Case Study from Peru

Abstract: Abstract. Surface-mediated disease transmission is understudied in developing countries, particularly in light of the evidence that surface concentrations of fecal bacteria typically exceed concentrations in developed countries by 10-to 100-fold. In this study, we examined fecal indicator bacterial contamination of dinner plates at 21 households in four periurban communities in the Peruvian Amazon. We also used surveys to estimate household use of and demand for surface disinfectants at 280 households. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…This is consistent with the literature demonstrating that non-dietary mouthing contacts are higher than dietary mouthing contacts [41,42]. Previous studies have demonstrated that soil in the domestic environment and on children's toys can be an exposure route to faecal pathogens [23][24][25], and that visibly dirty object-to- mouth contacts are associated with EE in young children [36]. However, despite the growing evidence, there are few interventions targeting this high-risk behaviour.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the literature demonstrating that non-dietary mouthing contacts are higher than dietary mouthing contacts [41,42]. Previous studies have demonstrated that soil in the domestic environment and on children's toys can be an exposure route to faecal pathogens [23][24][25], and that visibly dirty object-to- mouth contacts are associated with EE in young children [36]. However, despite the growing evidence, there are few interventions targeting this high-risk behaviour.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that soil is an exposure pathway for enteric infections [21,22]. Fomites such as children's toys and plates can also serve as transmission routes for enteric pathogens [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…coli concentrations may be due to E . coli contamination of laundry as observed in the United States and/or by use of soil or sand as a cleaning aid, as observed in Peru [ 36 , 37 ]. These findings further support the work of Pickering et al (2011) that shows female caretakers’ activities can dramatically influence their hand contamination [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, surfaces were found to harbor significant concentrations of fecal indicators, fomites, and diarrheal pathogens in Tanzanian 47 and Peruvian households. 48 Recently, published evidence has shown that environmental conditions in the household are linked to impaired childhood growth and other indicators of gut enteropathy in rural Bangladesh. 49 Unlike water quality studies, the collection of pathogens from surfaces is not standard practice in the water, hygiene, and sanitation research field, and the importance of household hygiene may have been underestimated in previous research as a result.…”
Section: Discussionmentioning
confidence: 99%